First records of Geastraceae and Nidulariaceae (Basidiomycota, Fungi) from Bahia, Northeastern Brazil - Trierveiler-Pereira, Larissa; Bezerra, Kátia Maria Trindade; Bezerra, José Luiz; Baseia, Iuri Goulart (Revista Brasileira de Biociências, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The state of Bahia has a great variety of tropical ecosystems, that harbour several interesting fungal species. Collections of gasteromycete specimens made from May/2005 to December/2006, in remnants of Atlantic Rain Forest, revealed interesting data. Six species of gasteromycetes, belonging to the families Geastraceae (Geastrum fimbriatum, G. hieronymi, G. lageniforme, G. saccatum and G. schweinitzii) and Nidulariaceae (Cyathus montagnei), were identified. All the species are new records from Bahia. Geastrum hieronymi is reported for the second time from Brazil and G. lageniforme is a new record from Northeastern Brazil.